2018
DOI: 10.1002/lsm.22934
|View full text |Cite
|
Sign up to set email alerts
|

A preclinical model to investigate the role of surgically‐induced inflammation in tumor responses to intraoperative photodynamic therapy

Abstract: The tumor incision model induces IL-6 release as is seen in the surgical setting, yet it avoids the limitations of surgical resection models. Potential mechanisms by which surgical induction of inflammation and IL-6 could alter the nature and efficacy of tumor response to PDT are reviewed. These include a wide spectrum of molecular and cellular mechanisms through which surgically-induced IL-6 could change the effectiveness of therapies that are combined with surgery. The tumor incision model can be employed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 106 publications
0
16
0
Order By: Relevance
“…These data indicate that IDO plays an important role in the regulation of immune tolerance to antigens released from dying cells and suggest that PDT-induced tumor cells death may be one of the triggers leading to increased immunopathology. IL-6 was previously shown to be induced by PDT in vitro and in vivo but also in cancer patients [31,35]. The reports on its impact on the antitumor efficacy of PDT were discordant showing either negative [36], positive [37] or no effect [38].…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that IDO plays an important role in the regulation of immune tolerance to antigens released from dying cells and suggest that PDT-induced tumor cells death may be one of the triggers leading to increased immunopathology. IL-6 was previously shown to be induced by PDT in vitro and in vivo but also in cancer patients [31,35]. The reports on its impact on the antitumor efficacy of PDT were discordant showing either negative [36], positive [37] or no effect [38].…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory mediators play a critical role in the activation and recruitment of immune cells at the irradiated tumor site. However, surgically induced IL‐6 is thought to have a negative impact on the efficacy of PDT . Here, we discuss how PDT induces immunostimulatory cell death that eventually leads to the activation of the adaptive immune system and antitumor immunity (Fig.…”
Section: Stimulation Of the Innate Immune Systemmentioning
confidence: 99%
“…These studies demonstrated that neutrophil activity is critical for tumor control under conditions in which direct tumor cell kill by PDT is not enough to provide for complete response. The clinical treatment of malignant pleural mesothelioma may represent one such scenario, as intraoperative PDT of mesothelioma generated an overall survival of 31.7 months despite a generally much earlier recurrence of disease .…”
Section: Introductionmentioning
confidence: 99%